CARBON TAX REGULATION IN INDONESIA: A COMPARATIVE REVIEW WITH SINGAPORE - Salsabila Yasmin Qanita; Sadiawati, Diani (Awang Long Law Review, 2025)
Climate change presents an urgent global challenge, prompting countries to adopt emission reduction strategies in accordance with the Paris Agreement. One such strategy is the implementation of a carbon tax to reduce greenhouse gas emissions and promote sustainable development. Indonesia and Singapore, as signatories to the Paris Agreement, have both introduced carbon pricing policies with differing legal and institutional frameworks. This study analyzes and compares the carbon tax regulations in Indonesia and Singapore to evaluate their alignment with climate commitments and identify practical lessons for Indonesia. The objective of this research is to examine the carbon tax regulations in both countries and identify aspects of Singapore's carbon tax policy that could serve as a lesson for Indonesia in formulating a more effective policy. This study employs a normative juridical method with a comparative approach and a statutory approach. The findings indicate that Indonesia’s carbon tax, introduced through Law Number 7 of 2021, represents an initial step toward achieving national climate targets. However, the policy is still limited in scope and lacks certainty in rate progression, coordination between institutions, and enforcement mechanisms. Conversely, Singapore’s Carbon Pricing Act 2018 provides a more structured and transparent system. It includes specific emission thresholds, gradually increasing tax rates, centralized reporting, and strict enforcement backed by legal sanctions. Therefore, Indonesia can draw lessons from Singapore in terms of policy design, institutional framework. These include establishing a clear carbon tax roadmap, improving inter-agency coordination, developing a centralized monitoring and reporting platform, and implementing firm sanctions for non-compliance.